Storytelling, behavior planning, and language evolution in context - McBride, Glen (Frontiers in Psychology, 2014)
An attempt is made to specify the structure of the hominin bands that began steps to language. 8 Storytelling could evolve without need for language yet be strongly subject to natural selection 9 and could provide a major feedback process in evolving language. A storytelling model is 10 examined, including its effects on the evolution of consciousness and the possible timing of 11 language evolution. Behavior planning is presented as a model of language evolution from 12 storytelling. The behavior programming mechanism in both directions provide a model of 13 creating and understanding behavior and language. Culture began with societies, then family 14 evolution, family life in troops, but storytelling created a culture of experiences, a final step in 15 the long process of achieving experienced adults by natural selection. Most language evolution 16 occurred in conversations where evolving non-verbal feedback ensured mutual agreements on 17 understanding. Natural language evolved in conversations with feedback providing 18 understanding of changes.